EFEKTIVITAS ZAKAT DALAM MENGURANGI KEMISKINAN DI JAWA TIMUR MENGGUNAKAN TEKNIK BASIC NEEEDS DEFICIENCY INDEX (BNDI) - Arum Fatmawati; Raditya Sukmana (Jurnal Ekonomi Syariah Teori dan Terapan, 2019)
This research aims to test the role of zakat to reduce poverty in the East Java period 2015-2017 by using the index that was recently developed, Basic Needs Deficiency Index. The research method used is qualitative approach with case study strategy. This research formulated BNDI index to measure the deficiency and effectiveness of zakat in resolving poverty. Data required is the total population that its income was below the poverty line in every city of East Java, and also total zakat, which was distributed by BAZNAS East Java in every city of East Java. The results obtained from the BNDI calculation have been able to explain the effectiveness of zakat for reducing poverty and inequality in East Java. The result of calculation, which was a high value or approaching value 1, explains that zakat that was distributed by BAZNAS East Java is not effective in reducing poverty in East Java. Furthermore, the result of this research shows that some cities had the highest BNDI and lowest BNDI as well. Hopefully, this result could be considered to use by the policymaker to improve the effectiveness of zakat in reducing poverty.Keywords: Zakat, Poverty, Basic Needs Deficiency Index (BNDI)REFERENCESBeik, Irfan Syauqi dan Laily Dwi. 2016. Ekonomi Pembangunan Syariah. EdisiRevisi. Depok: PT Rajagrafindo Persada.Creswell, John. W. 2015. Research Design Second Edition. Terjemahan oleh LintanLazuardi. Yogyakarta: Pustaka Pelajar.Dawson, Yelena. 2015. The Institutionalisation of Private Sector PerformanceMasurement in an Australian Oot-forprofit Organisation. epublications@scu.Fakultas Bisnis Administrasi. Southern Cross University.Fauzia, Amelia. 2008. Faith and a State: a History of Islamic Philanthropy inIndonesia. Disertasi tidak diterbitkan. Melbourne Faculty of Arts University ofMelbourne.Hafidhuddin, Didin. 2002. Zakat dalam Perekonomian Modern. Jakarta: Gema Insani.Hafidhuddin dan Rahmad Pramulya. 2008. Kaya Karena Berzakat. Depok : Raih AsaSukses.Huda, Nurul, dkk. 2012. Kebijakan Publik Islami. Jakarta: Kencana Prenada MediaGroup..Karim, Adiwarman Azwar. 2010. Sejarah Pemikiran Ekonomi Islam. Edisi Ketiga.Jakarta: Rajawali Press.BAZNAS Provinsi Jawa Timur, Profil BAZNAS, (Online), (www.baznasjatim.or.id 15 Agustus 2018. 20:17)Badan Pusat Statistik (Online), (www.bps.go.id 15 September  2018 20 12:43)Badan Pusat Statistik Provinsi Jawa Timur (online), (www.jatim.bps.go.id  15 september 2018 15:50)Indonesia Investment (online), (www.indonesia-investments.com 15 September 2018 16:30)Naziruddin, dkk. (2006). The Effectiveness of zakat in alleviating poverty and inequalities ( a measurement using a newly developed technique)